ASSESSMENT OF THE RELATION BETWEEN ARTERIAL STIFFNESS PARAMETERS AND ATHEROTHROMBOSIS FACTORS IN VARIOUS AGE GROUPS - N. V. Gomyranova; V. A. Metelskaya; O. N. Tkacheva; I. N. Ozerova; N. V. Perova; O. V. Alexandrovitch (Кардиоваскулярная терапия и профилактика, 2015)
Aim. To study the relation of pulse wave velocity (PWV) as arterial stiffness index, and the level of biochemical factors elevation, that are involved in atherothrombogenesis and play role in determination of cardiovascular risk in various age patients.Material and methods. Totally 202 patients included at the age 30-75 y.o. (M/F 68/134) without clinical signs of atherosclerosis. Stiffness/ elasticity of arteries was assessed by PWV method. Stiff — biologically "old" — we regarded the arteries with PWV more than 10 m/s, elastic — biologically "young" — in PWV <10 m/s. Biochemical parameters of the blood were assessed by standard methods.Results. In younger age group with stiff arteries comparing to those with elastic arteries there were higher levels of glucose, insulin, C-peptide and HOMA-IR. There was tendency revealed for higher levels of ultrasensitive C-reactive protein (hsC-rp) and fibrinogen. In older age group there were no differences in hsC-rp and fibrinogen, but the higher levels of glucose, C-peptide and HOMA-IR found with the same level of insulin. In comparison of different age groups with elastic arteries in older group we found higher levels of fibrinogen and von Willebrand factor, and tendency for higher level of hsC-rp. In persons with stiffer arteries >45 y.o. von Willebrand factor and fibrinogen also were higher. In comparison of different age groups with elastic and stiff arteries we found higher levels of glucose and glycosylated hemoglobin with the same levels of insulin, C-peptide and HOMA-IR. Conclusion. Increased PWV non-dependent of age is associated with disruptions of carbohydrate metabolism as decreased insulin sensitivity. Accelerated biological ageing (increased PWV in younger age group) is associated not only with significant alterations in glucose utilization processes, but also with initial signs of chronic inflammation of arterial wall and tendency to clot formation.